(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
The generic and indiscriminate application of the informal review envisaged in article 40 CCyC leads to unreasonable results that obscure the tuitive purpose of the norm. Thus, the very short term of three years does not benefit people with severe and chronic mental illnesses whose disability has been declared by judicial decision, as they are subject to judicial processes virtually for life, affecting in some way the right to be judged within a reasonable time and therefore the due process guarantee. In addition, it harms the provision of a good justice service, at the same time as it causes an unnecessary waste of jurisdictional resources. Therefore, it would be advisable to limit the frequency of this review according to the particular circumstances of each case, either as from a review and possible reform of the basic legislation or, in the meantime, by declaring the Art unconstitutional 40 CCC.